Racial and Community Wealth Disparity the Bane of HBCUs - A Wealth Ecology Model Relational Perspective (Global Journal of Management and Business Research, 2021)
Racial wealth disparities in US continues to persist despite community state and federal governments programs to arrest the slide Contemporary community wealth creation approaches using anchor institutions concepts to bridge the gap assumes the wealth improvement duality of the community and the anchor institution coming together with external agents of support
Keywords: racial wealth disparity; median household wealth; anchor mission; behavioral intention; school choice